Loan Growth, Bank Solvency and Firm Value: A Comparative Study of Nigerian and Malaysian Commercial Banks - Ebenezer, Olalere Oluwaseyi; Islam, Md. Aminul; Junoh, Mohd Zukime Mat; Yusoff, Wan Sallha (Journal of Reviews on Global Economics, 2019)
The study explore the issues relating to credit growth, non-performing credit and bank solvency in the banking industry, recognizing that existing studies are largely sketchy in emerging and developing markets. Panel data estimation technique is employed in the study based on data extracted from 26 commercial banks in Nigeria and Malaysia over the period 2009 to 2017 making up to 234 observations. The results reveal that the NPLs for all banks is only explained by loan growth and inflation, NPLs for Nigerian banks is only explained by loan growth, leverage, efficiency, size and inflations while NPLs for Malaysian banks is only explained by leverage, efficiency, size, GDP and inflation. The bank solvency for all banks is only explained by NPLs, loan growth and leverage. The solvency for Nigerian banks is explained by NPLs, leverage and GDP while loan growth, size and inflation explained bank solvency for Malaysian banks. Firm value for all banks is explained by solvency, NPLs, leverage, efficiency, size and GDP, the value of firm for Nigerian banks is only explained by solvency, loan growth, leverage, efficiency and size. The firm value for Malaysian banks is only explained by solvency, loan growth, leverage, efficiency, size, GDP and inflation. It is observed that bank solvency play an important role in the firm value of commercial banks in the period of study. Hence, this paper contributes to the understanding of the dynamic role of abnormal loan growth and how it can enhance the volume of non-performing credit and suggest that further study can explore the interaction between abnormal loan growth and non-performing loans.